Application of the K-Means Algorithm to Segmentation of Consumer Interest in Silver Craft "Kreasi Slaka Bali" - Putri, I Gusti Ayu Widiantari; Dwidasmara, Ida Bagus Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 9 No 4 (2021): JELIKU Volume 9 No 4, Mei 2021DO - 10.24843/JLK.2021.v09.i04.p12, 2021)
Kreasi Slaka Bali is a company engaged in the silver handicraft sector. Each stage of the process is still done manually, starting from material preparation, handmade work, until making the packaging for delivery. Certainly, this requires more time to be able to produce an item of the same quality in each production. The need for extra time and business in product manufacturing, the company needs a marketing strategy that can be seen from consumer interest in the product. So this research discusses consumer interest based on transaction data by forming clusters based on purchases amount with other attributes, namely the product price, product size, product weight, and level of difficulty. The data used is transaction data for 2 transactions in 2019. The algorithm used is K-Means with the Elbow Method to determine the number of clusters. There are clusters of k = 5 with the cluster that has the most data in the first cluster (k = 0) with a total purchase of 193 products with an average price of US $ 69,554688.